War Imprisonment and Clinical Narratives of Psychiatric Illness, Psychiatric Hospital Charité, Berlin, 1948–1956. (9th January 2019) - Schöhl, Stephanie; Hess, Volker
Abstract: While the historical analysis of psychological trauma from warfare has been extensive, traumatic illness in East German psychiatric practice after the Second World War has drawn little attention. The dominant literature uses West German political and medical discourses as sources to investigate the relationship between traumatic experience and psychiatric illness. This paper instead draws from East German patient files from 1948 until 1956 to examine efforts at the Charité Hospital in Berlin to interpret the psychiatric illness of former prisoners of war (POWs). By examining Socialist Party discourse at the time, the paper argues that psychiatric explanations created parallels with political debates by foregrounding social readjustment difficulties as the cause of postwar illness. Against this background, the final section explores the way in which war imprisonment could constitute a challenge to the clinical restructuring of former POWs' patient histories. Using strategies of confabulation, POWs confronted the documentary negotiation between bodies and meaning, provoking ambivalence.